2010
DOI: 10.1590/s1809-48722010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil audiológico de pilotos agrícolas

Abstract: Introduction:The agricultural airplane pilot are daily exposed to intense noises, being susceptible to the noiseinduced hearing loss (NIHL) and its auditory and extra auditory effects. Objective:To analyze the audiological profile of this population, verifying the work's influence on its hearing. Method:It was realized a retrospective, individual, observational, and cross-sectional study through the data obtained by means of a questionnaire and audiometric thresholds of 41 agricultural pilots. To the statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
9
0
4
Order By: Relevance
“…Estudos revelaram os benefícios do uso da AAF no diagnóstico da perda auditiva associada a agentes físicos e químicos [30][31][32][33][34][35][36][37] e pesquisas sinalizam para a possibilidade do efeito ototóxico dos agrotóxicos 6,23,28,29,31,[37][38][39][40][41] , entretanto nenhum trabalho relacionando, exclusivamente, a exposição aos agrotóxicos e a realização de AAF foi encontrado.…”
Section: Discussionunclassified
“…Estudos revelaram os benefícios do uso da AAF no diagnóstico da perda auditiva associada a agentes físicos e químicos [30][31][32][33][34][35][36][37] e pesquisas sinalizam para a possibilidade do efeito ototóxico dos agrotóxicos 6,23,28,29,31,[37][38][39][40][41] , entretanto nenhum trabalho relacionando, exclusivamente, a exposição aos agrotóxicos e a realização de AAF foi encontrado.…”
Section: Discussionunclassified
“…In addition, 29.3% pilots had suspected NIHL, which is a significant number, as corroborated by Harger & Barbosa-Branco 7 (2004), Silva et al 11 (2004), Gerostergiou et al 6 (2008), and Foltz et al 4 (2010). In contrast, Lindgren et al 8 (2009) found no indication that the cabin crew of a Swedish commercial airline company had increased rates of hearing loss compared with a population of the same country not exposed to noise, despite the relative exposure to high noise levels.…”
Section: Discussionmentioning
confidence: 71%
“…Gerostergiou et al 6 (2008) conducted a study involving 15 pilots of the Larissa Aeroclub in Greece and observed that 30.0% pilots experienced hearing impairments suggestive of NIHL. A retrospective, observational, and cross-sectional study evaluated 41 agricultural pilots 4 and reported a high prevalence of hearing loss, although > 50.0% pilots had normal hearing threshold levels with slot configuration. Agricultural pilots, even wearing personal protective equipment (PPE) (95.1% made use of PPE during flight), suffer hearing impairments caused by noise and lack better alternatives for the prevention of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important but were not confirmed in this research. The reason may be the hearing health mantainence depends on set of factors as the quantity and the frequency of pesticides exposition, the concurrent operating noise equipment, and the lack of individual protection 4,8,[23][24][25] ; in the current research, most subjects operated noise equipment at work, handled pesticides, and used individual protection device (Table 3). These findings are different from other studies 5,10 of the same theme, because most farmers reported not using the protection device for several reasons, as: financial issues to acquire the individual protection device, troubles using it due to warmth, discomfort and lack of habit to use it 10,23 .…”
Section: Discussionmentioning
confidence: 82%